THE INFLUENCE OF ONLINE FOOD DELIVERY BRAND EXTENSIONS ON BRAND PREFERENCE IN E-COMMERCE APPLICATIONS - Pandya, Raden Mochamad Ariandi Putra; Istiharini, Istiharini (UPT Publikasi Ilmiah UNISBA, 2024)
Go-Jek and Grab are examples of e-commerce applications. They offer similar features from brand extensions that help people meet their daily needs. This research will further explore the influence of online food delivery brand extensions on brand preference. The research method used in this study is applied research with both qualitative and quantitative data. Data were obtained through a questionnaire distributed to 154 respondents who had used the Go-Jek and Grab e-commerce applications. The research employed descriptive, explanatory, and statistical techniques for data processing. This research consists of independent variables (brand extension) and dependent variables (brand preference). Analysis used linear regression and classical assumption tests to obtain research conclusions. This research shows that brand extension online food delivery, with the dimensions of similarity, reputation, perceived risk, and innovativeness, has an influence on brand preference, accounting for 26.8% on the Go-Jek application and 42% on the Grab application. Keywords : Brand extension, Brand Preference, e-commerce